2000
DOI: 10.1103/physreva.61.033414
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton radiative recombination of electron assisted by a laser field

Abstract: In the presence of an intensive laser field the radiative recombination of the continuum electron into an atomic bound state generally is accompanied by absorption or emission of several laser quanta. The spectrum of emitted photons represents an equidistant pattern with the spacing equal to the laser frequency. The distribution of intensities in this spectrum is studied employing the Keldysh-type approximation, i.e. neglecting interaction of the impact electron with the atomic core in the initial continuum st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The value has recently been supported by a calculation by Kuchiev and Ostrovsky, which uses a different approach to the problem. This theory also predicts a power law dependence as in (5), and they find a value a 3.838 [20] in good agreement with the result of Mendez and Feagin. Rost and Pattard [21] have shown that for single ionization it is possible to incorporate the threshold behavior of the Wannier theory with the high energy behavior of the first Born approximation to form a parametrization depending only on the Wannier exponent.…”
Section: Strong Suppression Of the Positronium Channel In Double Ionisupporting
confidence: 85%
“…The value has recently been supported by a calculation by Kuchiev and Ostrovsky, which uses a different approach to the problem. This theory also predicts a power law dependence as in (5), and they find a value a 3.838 [20] in good agreement with the result of Mendez and Feagin. Rost and Pattard [21] have shown that for single ionization it is possible to incorporate the threshold behavior of the Wannier theory with the high energy behavior of the first Born approximation to form a parametrization depending only on the Wannier exponent.…”
Section: Strong Suppression Of the Positronium Channel In Double Ionisupporting
confidence: 85%
“…(3) the integral over time in (28) is evaluated using the saddle point method. As a result, for d (dr) n we obtain (cf.…”
Section: Low-frequency Results For the "Direct" Labrs Amplitude D (Dr) Nmentioning
confidence: 99%
“…given by (16). The result for the dipole moment d(rsc) n then follows from (28) after substituting there the "rescattering approximations" for L (1,2) (t). The result can be presented in the form:…”
Section: Of the Labrs Amplitudementioning
confidence: 99%
“…The necessary matrix element is contributed by entire range of electron-core separation r. This circumstance was noticed for LAR process in Ref. [29] and for HHG in Ref. [9].…”
Section: Introductionmentioning
confidence: 82%